Foot-and-mouth disease: genomic and proteomic structure, antigenic sites, serotype relationships, immune evasion, recent vaccine development strategies, and future perspectives - Alyaa Elrashedy; Mohamed Nayel; Akram Salama; Ahmed Zaghawa; Rehan M. El-Shabasy; Mohamed E. Hasan (Veterinary Research)
Abstract Foot-and-mouth disease (FMD) is a highly contagious and transmissible disease that can have significant economic and trade repercussions during outbreaks. In Egypt, despite efforts to mitigate FMD through mandatory immunization, the disease continues to pose a threat due to the high genetic variability and quasi-species nature of the FMD virus (FMDV). Vaccines have been crucial in preventing and managing FMD, and ongoing research focusses on developing next-generation vaccines that could provide universal protection against all FMDV serotypes. This review thoroughly examines the genetic structure of FMDV, including its polyprotein cleavage process and the roles of its structural and non-structural proteins in immune evasion. Additionally, it explores topics such as antigenic sites, specific mutations, and serotype relationships from Egypt and Ethiopia, as well as the structural changes in FMDV serotypes for vaccine development. The review also addresses the challenges associated with creating effective vaccines for controlling FMD, particularly focusing on the epitope-based vaccine. Overall, this review offers valuable insights for researchers seeking to develop effective strategies and vaccines for controlling FMD.